Abundance of Atlantic walrus in Western Nares Strait, Baffin Bay Stock, during summer - Stewart, Robert EA; Born, Erik W; Dietz, Rune; Heide-Jørgensen, Mads Peter; Rigét, Frank Farsø; Laidre, Kristin; Jensen, Mikkel Villum; Knutsen, Lars Ø; Fossette, Sabrina; Dunn, J B (NAMMCO Scientific Publications, 2014)
Atlantic walruses (Odobenus rosmarus rosmarus) belonging to the Baffin Bay subpopulation occur year round in the North Water polynya (NOW) between NW Greenland and eastern Ellesmere Island (Canada). They are hunted for subsistence purposes by residents of the Qaanaaq area (NW Greenland) bordering the NOW to the east and by Canadian Inuit at the entrance to Jones Sound in Nunavut. During the open-water period NW Greenland is virtually devoid of walruses which concentrate along eastern and southern Ellesmere Island at this time of the year. To determine the abundance of walruses in the NOW area, aerial surveys were conducted in August of 1999, 2008, and 2009. In July 2009, nine satellite-linked transmitters were deployed in nearby Kane Basin. Surveys on 9 and 20 August 2009 along eastern Ellesmere Island were the most extensive and were augmented with concomitant data on haul-out and at water surface activity from three (1 F, 2 M) of the nine tags that were still functioning. We therefore focus on the 2009 surveys. Walruses were observed on the ice and in water primarily in Buchanan Bay and Princess Marie Bay where the remaining functional tags were located. The Minimum Counted population (MCP) was 571 on 20 August. Adjusting the MCP of walruses on ice for those not hauled out, the estimate of abundance of walruses in the Baffin Bay stock was 1,251(CV=1.00, 95% CI = 1,226) when adjusted by the proportion of tags ‘dry’ at the time of the survey and 1,249 (CV=1.12, 95% CI = 1,370) when adjusted by the average time tags were dry. The surveys did not cover all potential walrus summering habitat along eastern Ellesmere Island and are negatively biased to an unknown degree.